ADP secreted by dying melanoma cells mediates chemotaxis and chemokine secretion of macrophages via the purinergic receptor P2Y12 - Kloss, Loreen; Dollt, Claudia; Schledzewski, Kai; Krewer, Andreas; Melchers, Susanne; Manta, Calin-Petru; Sticht, Carsten; Torre, Carolina de la; Utikal, Jochen; Umansky, Viktor; Schmieder, Astrid (Cell death & disease, 2019)
Melanoma immunotherapy is still not satisfactory due to immunosuppressive cell populations within the tumor stroma. Targeting tumor-associated macrophages (TAM) can help to restore an anti-tumor immunity. Previously, we could show that classical TAM markers expressed in vivo need a 7 day M-CSF/dexamethasone/IL-4 (MDI) stimulation for their induction in peripheral blood monocytes (pBM) in vitro. To identify possible novel therapeutic targets on TAM, gene expression analysis of MDI-treated pBM was performed. This identified up-regulation of the purinergic G-protein coupled receptor P2Y12, the therapeutic target of the clinically approved anti-thrombotic drugs cangrelor, clopidogrel, ticagrelor, and prasugrel. We generated a peptide antibody and validated its specificity using transgenic P2Y12+ U937 cells. With the help of this antibody, P2Y12 expression was confirmed on CD68+ CD163+ TAM of melanoma in situ. Functional analysis revealed that treatment of transgenic P2Y12+ U937 cells with the receptor agonist 2-MeSADP induced ERK1/2 and Akt phosphorylation and increased the secretion of the chemokines CXCL2, CXCL7, and CXCL8. These effects could be abolished with the P2Y12 antagonist PSB0739 or with Akt and ERK inhibitors. In addition, P2Y12+ macrophages migrated towards the ADP-rich culture medium of puromycin-treated dying B16F1 melanoma cells. Cangrelor treatment blocked migration. Taken together, our results indicate that P2Y12 is an important chemotaxis receptor, which triggers migration of macrophages towards nucleotide-rich, necrotic tumor areas, and modulates the inflammatory environment upon ADP binding.